Sex, Sensibility and the Gendered Body
XI, 248 p.
Keywords: The study of sexuality is moving from margin to centre stage in sociology, as the 1994 British Sociological Association annual conference on 'Sexualities in Social Context' demonstrated. Drawn from that conference, the papers in this volume contribute to the debates which have developed on the relationship between the sexual and the social, and between gender and sexuality. The focus is on women, and from different perspectives the authors explore the themes of gendered identity, the construction of sexuality, embodiment and control. The social contexts in which these themes are elaborated include the family, the law, the education system, medical practice and discourse, and cultural representations and texts.